A Study Of Learned Optimism And Managerial Effectiveness In Sales Personnel - Hyde, Anukool Manish; Shrivistava, Shilpi; Arora, Swaranjeet (Gyan Management Journal, 2010)
Learned optimism (LO) is a sense of enthusiasm, confidence and control, and these develop when one achieving successes. The intimate connection between achievable goals and optimism can be the conceptof"Learned Optimism’’. In general, optimism is used to denote a positive attitude or : :-: ,: . on that good thing will happen independent of one’s ability. Managerial effectiveness ME) is defined as the manager’s ability to deal with different situations, which he faces from: - , : : time. The present exploratory study has been conducted with a sample size of 140 sales :- -.- : —.el having experience of at-least one year. Respondents are from automobile, pharmaceutical, . · - = :; ,d insurance sectors. Scales have been used for data collection and z-test, correlation are used analysis. Z results are showing significant difference in LO and ME between pharmaceutical 7lobilesectors,Jnsuranceandtextilesector.